CHANGES IN THE SPATIAL ORGANISATION OF FRUIT GROWING AT THE BEGINNING OF THE 21ST CENTURY: THE CASE OF GRÓJEC POVIAT (MAZOVIA VOIVODESHIP, POLAND) - Wójcik, Marcin; Traczyk, Anna (Quaestiones Geographicae, 2017)
This paper is meant to determine trends in changes in the organisation of fruit production at the beginning of the 21st century. It focuses on the determination of those trends as well as their circumstances. The analysis of changes in the organisation of fruit production was made using Grójec poviat as an example. The accession of Poland to the European Union resulted in the intensification of processes of specialisation and concentration in agriculture, due to which the area occupied by orchards started to grow systematically. With the growing area and the intensification of fruit crops, quantities of fruits produced also increased. Currently, Poland is one of the biggest fruit manufacturers in Europe, with Grójec poviat being the biggest producer in Poland.